PENGARUH KOMPOSISI BAHAN PENGENDALI TERHADAP PERTUMBUHAN JAMUR Uromycladium tepperianum PADA TEGAKAN SENGON (Falcataria mollucana) - Kusumaningsih, Karti Rahayu; Bagaskara, Isnaya Fatul (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2019)
One problem in Falcataria mollucana cultivation is attack of gall rust disease caused by Uromycladium tepperianum fungi. This disease attack almost all parts of tree, so can detain the growth and cause death of tree. The efforts to control this disease always be tried, but until now its result is not satisfactory. Purpose of this study is to know effect of controlling materials composition against growth of U. tepperianum fungi as cause of gall rust disease at F. mollucana. The research used completely randomized design with controlling materials composition as treatment factor, namely lime, sulphur, mix of lime and sulphur solution, and tar solution. Observed parameters were percentage of U. tepperianum weight reduction and diameter increased of F. mollucana after one month treatment. Result of the research showed that controlling materials composition gived significant effect to percentage of fungi weight reduction, but was not significant effect againts diameter increased of F. mollucana. Tar solution resulted highest percentage of fungi weight reduction than others controlling materials, with 100% score (fungi did not grow again after treatment). Keywords: Uromycladium tepperianum, gall rust disease, controlling materials composition